Platelet Parameters in Nonthrombocytopenic Preeclampsia: A Case-Control Study - Alhusaynei , Ahmed J.; Nayyef, Hanan Dh (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Preeclampsia is a pregnancy-specific, multisystem condition characterized by the onset of de novo hypertension and proteinuria occurring in previously normotensive women after the twentieth week of pregnancy. Pregnancy is associated with a physiological adaptation that leads to changes in the hematological system including platelet parameters.                                     Objectives: Is to compare platelet count, and platelet indices, namely mean platelet volume platelet distribution width and platelet count to mean platelet volume MPV ratio in preeclamptic patients with normal pregnant women.           Patients & methods: A case-control study was carried out in the obstetrics and gynecology department at Al-Khansaa Maternity and Childhood Teaching Hospital, Mosul, Iraq over a period extending from February 2020 to the end of December 2020. A sample of 120 pregnant women participated in the study fulfilling inclusion criteria. Sixty of them were diagnosed with preeclampsia PE (30 pregnant women with mild PE and 30 pregnant women with severe PE) and sixty healthy pregnant women as the control group. Platelet count, mean platelet volume, and platelet distribution width (PDW) were measured and statistical analysis by mini tab program was done for all collected data.Results: A significant linear correlation between mean platelet volume (MPV) and platelet distribution width (PDW) with mean arterial pressure in the Preeclampsia group with p-value of (0.025 and 0.001) respectively and a significant inverse correlation between the platelet count and mean arterial pressure with a p-value of (